2022
DOI: 10.5137/1019-5149.jtn.36243-21.2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rehabilitation following anterior cervical microdiscectomy and fusion surgery

Abstract: AIM:To determine the effects of physical therapy and exercise programs that was performed after anterior cervical discectomy and fusion (ACDF) surgery on patient's pain treatment, a retrospective study was designed. MATERIAL and METHODS:Of the 127 patients without neurological deficit who underwent ACDF surgery in our clinic in 2019 and 2020 for single-level cervical disc herniation, 40 patients (including 23 men and 17 women) were enrolled. The mean age of the patients was 45.5 years. The patients were separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Cerezci et al, also in their study, described ODI ranging from 86% to 20% in the pre-and post-operative periods, respectively, demonstrating statistical significance in the result. 19 The present study also found statistically significant figures ranging from 80% in the pre--operative period to 18% in the third postoperative month.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Cerezci et al, also in their study, described ODI ranging from 86% to 20% in the pre-and post-operative periods, respectively, demonstrating statistical significance in the result. 19 The present study also found statistically significant figures ranging from 80% in the pre--operative period to 18% in the third postoperative month.…”
Section: Discussionsupporting
confidence: 79%
“…18 In their case series, Cerezci et al described a variation in cervical VAS from 10 preoperatively to 1 postoperatively. 19 In our study, we found a significant variation in the two groups, ranging from 8 preoperatively to 1 postoperatively from the third postoperative month onwards. Cerezci et al, also in their study, described ODI ranging from 86% to 20% in the pre-and post-operative periods, respectively, demonstrating statistical significance in the result.…”
Section: Discussionmentioning
confidence: 45%
“…Both interventions significantly improved symptoms from baseline in most of the studies, with no inter-group significant difference. Current evidence demonstrates that any therapy is superior to no intervention postoperatively for cervical spondylosis patients following cervical fusion [ 32 ]. This systematic review, demonstrating equivocal improvement in patient outcomes between augmented or targeted therapy and standard postoperative therapy for patients with cervical spondylosis following cervical fusion, is consistent with the current evidence [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…Postoperative therapy has been demonstrated to improve outcomes without deleterious effects on instrumentation in cervical fusion [ 32 ]. In this systematic review, augmented and targeted therapies improved patient catastrophizing and satisfaction postoperatively, particularly in the Coping Strategies Questionnaire - Catastrophizing Scale (CSQ-CAT) score.…”
Section: Reviewmentioning
confidence: 99%
“…The current literature evaluating the benefits of post-operative PT using patient-reported outcomes (PROs) is limited and remains inconclusive [17][18][19]. Additionally, PROs have historically been measured using such tools as general health questionnaires (Medical Outcomes Study Short Form), pain rating scales (VAS), or disease-specific questionnaires (NDI, Oswestry Disability Index).…”
Section: Introductionmentioning
confidence: 99%